KAJIAN PENGGUNAAN MEDIA DALAM PROSES PEMBELAJARAN MATEMATIKA DI KELAS 1 SD NEGERI 066056 - Mila Rossi Finka M; Selvi Rola Aulia Siburian; Ayu Oktafia Saragih; Elvi Mailani (Universitas Negeri Medan, 2025)
Mathematics is a core subject in elementary school that has an important role in building students' logical, critical, and creative thinking skills. Learning media is considered an effective alternative to improve students' understanding and interest in learning. The purpose of this study was to identify the learning media applied by teachers and to analyze the difficulties experienced by teachers in their application and the responses given by students to the use of learning media in class 1 of SD Negeri 066056. The research method used was Observational research using a Qualitative Approach, involving direct observation of the subject to be carried out carefully. The results of the study showed that real object and replica learning media were very useful in helping students understand the learning material and the responses given by students were also very enthusiastic. However, the obstacles faced by teachers are still there, namely the lack of learning media.